(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Packaging is considered as an integral part of the ’Product’ of marketing mix. Along with basic objectives (protection and preservation, containment, convenience and communication) packaging serves as a promotional tool. Packaging is an important part of the branding process as it plays a vital role in communicating the image and identity of an organization. The objective of this study is to find out role of packaging in brand communication and determining the elements/attributes of packaging for communicating the brand value to customers. To pursue these objectives the authors have developed a research framework for packaging which furcates the main objective into four sub-objectives namely dependence of packaging design upon the buyer attraction, communication to buyer, convenience in handling and using, saleability of product and green aspect; relationships between liking for package and brand, country of origin, colour connotation, symbol connotation and size; relationships between communication through the package and independent variables like information, shape, brand image and symbols/logos; relationship between usability of package and ease of handling, disposability and protection. Data is collected through questionnaire along with the measurement of pulse rate of respondents with the help of pulse oxy-meter. Reliability test is carried out for questionnaire’s consistency and then multiple regression analysis is done to formulate relationship between dependent variable and independent variables. This research reveals the importance of buyer attraction in package design and unimportance of environmental considerations. Similarly customers are more likely to give weightage to branded product than to the package and shape of package is the significant attribute of communication through product packaging.